RELIGIOSITY AMONG WORKING CLASS ( A Study of the implementation of Act No. 13 of 2003 on Manpower in The Rights to Perform Religious Obligations - Ikhwan Aulia Fatahillah; Dadan Anugrah (International Journal of Nusantara Islam, 2019)
The implementation of Act No. 13 of 2003 on Manpower is intriguing to discuss since companies often violate and are apathetic in the right to act for employees' religious beliefs. The limited facilities of worship in the workplace also represents the commitment engagement of the company towards promulgated regulations which is still not implemented.The purpose of this study is to provide the more specified description and understanding towards the religiosity and implementation of Act No. 13 of 2003 on Manpower concerning The Rights to Perform Religious Obligations for Laborers. This study, which focuses on the religiosity of this worker class, took two different places, namely in Bekasi Regency and Subang Regency.This study uses qualitative methods which enables to reveal the actual circumstances. More specifically, qualitative research can be identified by the aim of research that seeks to understand the manifestation that does not require quantification--or because this manifestation is unable to be accurately measured. In relation to the method, the data collecting techniques are as follows: (1) nonparticipant observation and (2) in-depth interviews. While the data analysis starts from (1) data reduction, (2) data presentation, and (3) drawing conclusions.By this study, the authors concluded: (1) companies that have become research object in Bekasi and Subang District have provided worship facilities and infrastructure as regulated in Act N. 13 of 2003 on Manpower in the Respect to Perform Religious Obligations. On the other hand, the workers still look forward some improvements on quality and quantity of worship facilities to emerge conveniences in performing worship; and (2) in general, the religiosity among working class is found at an average level.  In other words, the workers truly believe in God (Allah) with common knowledge about faith. They also perform religious practices as the evidence of the faith itself and as proof of obedience to God. Besides carrying out the orders of religion (worship), the workers also put some expectations on the reward as the way to accomplish the glory on Earth and afterlife. However, the workers realize that the worship carried out would not come to a subjective perspective (their dialogue with supernatural powers, Allah). The workers also attempt to make religion as the basis of all actions as they consider the consequences of the life on Earth for the afterlife.